BENTUK DAN JENIS PUISI PRISMATIS DALAM KUMPULAN PUISI AIR KATA KATA KARYA SINDHUNATA - Siti Fatimah (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2013)
The use of the term is less commonly used prismatic poetry when its existence can not be covered or removed from the history of poetry in indonesia. Thus, it is necessary to do the analysis or in-depth study of the works which can be categorized into these types of poetry. The analysis is based on the problem of "how the prismatic shape and kind of poetry is in the air kata kata by sindhunata?" the purpose of this study is to determine the shape and type of prismatic poetry is in the air kata kata by sindhunata.Used a qualitative descriptive approach in the analysis of prismatic shape and kind of poetry in the collection of poems air kata kata by sindhunata. The focus of the study conducted on 1) forms, 2) the substance, 3) themes, 4) type, and 5) language to obtain forms and types that exist in the poetry collection.Based on the analysis, it can be said that 1) form prismatic poetry is in the air kata kata is a combination of text and images in one frame, and 2) the type of prismatic poetry is in the air kata kata classified by theme, diction is used, the type of language used, and typography. Thus, it can be concluded that the prismatic shape and kind of poetry that is in the collection of poems can be classified into a new genre, there are two kinds, namely poetry mbeling (physical structure and inner unconventional) and poetry rinupa (a blend of poetry texts and images), therefore, the analysis can be carried out or continued research in the field of poetry prismatic especially on matters relating to poetry and poetry mbeling rinupa.